Early motor unit conduction velocity changes to high-intensity interval training versus continuous training - Martinez-Valdes, E.; Farina, D.; Negro, F.; Del Vecchio, A.; Falla, D. (Medicine & Science in Sports & Exercise, 2018)
Purpose Moderate-intensity continuous training (MICT) and high-intensity interval training (HIIT) are associated with different adjustments in motor output. Changes in motor unit (MU) peripheral properties may contribute to these adjustments, but this is yet to be elucidated. This study evaluated early changes in MU conduction velocity (MUCV) and MU action potential amplitude after 2 wk of either HIIT or MICT.